Do You Really Know if It’s True? How Asking Users to Rate Stories Affects Belief in Fake News on Social Media - Moravec, Patricia L.; Kim, Antino; Dennis, Alan R.; Minas, Randall K. (Information Systems Research, 2022)
Research shows that consuming ratings influences purchase decisions in e-commerce and also has modest effects on belief in news articles on social media. We find that the act of producing ratings reduces belief in news articles on social media and induces social media users to think more critically. We propose this intervention as a method to encourage users to realize that, unlike in the product rating setting, social media users who submit their ratings for news articles typically lack firsthand knowledge of the events reported in the news, making it difficult for most users to rate news articles accurately. We asked 68 social media users to assess the believability of 42 social media articles and measured their cognitive activity using electroencephalography. We found that asking users to rate articles using a self-referential question induced them to think more critically—as indicated by increased activation in the medial prefrontal cortex and dorsolateral prefrontal cortex—and made them less likely to believe the articles. The effect extended to subsequent articles; after being asked to rate an article, users were less likely to believe other articles that followed it whether they were asked to rate them or not.